F-35 Hits Tank In First Drop Of Guided Bomb On A Target - McCarthy, Mike (Defense Daily, 2013)
An F-35 dropped a guided bomb on a stationary tank this week, marking the first time the Joint Strike Fighter has struck a target on the ground, the Pentagon said yesterday. <nitf-col value=""/> </nitf-table-metadata> The F-35B Marine Corps short-takeoff and vertical-landing (STOVL) variant of the fighter released a 500-pound GBU-12 Paveway II laser-guided bomb against the tank during the test Tuesday in California's Mojave Desert. The GBU-12, however, was not carrying ordnance and therefore was not considered a live fire test, F-35 program spokesman Joe DellaVedova said.